Gender Differences in the Relationship Between Mathematical Disposition and Problem-Solving Skills - Mubarokah, Hevi Haplatul; Dewi, Sinta Verawati; Depi Setialesmana (Education and Talent Development Center Indonesia (ETDC Indonesia), 2025)
Mathematical disposition, which encompasses students’ confidence, perseverance, curiosity, and appreciation toward mathematics, plays a significant role in shaping their approaches to problem-solving. This study aims to investigate gender-based differences in students’ mathematical disposition and problem-solving ability, and to analyze the overall relationship between these variables. A quantitative approach employing a comparative–correlational design was used. Following Yount’s sampling guideline, 10% of the population (comprising 39 seventh-grade students) was randomly selected through simple random sampling. Research instruments included a Likert-scale questionnaire to measure mathematical disposition and an essay-based test developed from the IDEAL problem-solving framework. Both instruments were previously validated and tested for reliability to ensure data accuracy. Data were analyzed using an independent-samples t-test and Spearman’s rank correlation. Results revealed no significant difference in mathematical disposition between male (M = 67.26) and female students (M = 65.65), t(37) = 0.553, p > 0.05. In contrast, a significant difference was found in problem-solving ability, with male students (M = 69.42) outperforming females (M = 56.70), t(37) = 2.77, p < 0.05. Moreover, a low positive correlation (ρ = 0.2172) was observed between mathematical disposition and problem-solving ability. These findings suggest that gender factors may influence students’ cognitive and affective engagement in mathematical problem-solving. The study contributes to the growing body of research on mathematics education by emphasizing the importance of integrating affective and cognitive dimensions in designing more personalized and effective teaching practices